Raised-Relief Map Training: a Creative Geography Learning Media for Junior High School Social Studies (IPS) Teachers - Affandri Jasrio; Deded Chandra; Helfia Ideal; Eva Purnama Sari; Ratna Wilis; Bambang Afriadi Putra; Dila Andriani; Ibnu Fadhil Azzikri; Regi Cania; Cindy Dian Hadisty (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Teaching Indonesia’s geographical conditions in schools often faces challenges because flat maps are insufficient to represent topographic variations realistically. As a result, junior high school social studies teachers (SMP/MTs) struggle to explain differences between highlands, lowlands, and water bodies, making it difficult for students to fully understand. To address this issue, a training program on making embossed maps was carried out for members of the Social Studies Teachers’ Association (MGMP) in Padang City. The focus was not on students directly, but on enhancing teachers’ competencies so they can design and apply innovative learning media in the classroom. Embossed maps were created through several steps: (1) drawing a map sketch on plywood, (2) layering newspaper pulp to follow the topographic contours, (3) drying the map under sunlight, (4) coloring according to elevation, and (5) preparing a legend that reflects relevant geographic elements. The training demonstrated high enthusiasm among participants, who successfully produced embossed maps as effective visual media. Thus, embossed maps should be strongly advocated as practical, innovative, and applicable tools to support effective geography teaching and learning in social studies.